Adaptation of the Aphasia Impact Questionnaire-21 into Greek: A Reliability and Validity Study - Charalambous, Marina; Phylactou, Phivos; Kountouri, Alexia; Serafeim, Marios; Psychogios, Loukia; Annoni, Jean-Marie; Kambanaros, Maria (My University, 2022)
The impact of aphasia on the everyday life of Greek-speaking people with aphasia (PWA) is often underestimated by rehabilitation clinicians. This study explores the adaptation and psychometric properties of the Greek (GR) version of The Aphasia Impact Questionnaire-21 (AIQ-21-GR) to address this issue. The aim of this study is to determine the reliability and validity of the Greek version of the AIQ-21. The AIQ-21-GR was administered to 69 stroke survivors, 47 with aphasia and 22 without aphasia. The data were analyzed to determine reliability and validity. Content validity was based on the Consensus-based Standards for the selection of health Measurement Instruments guidelines. The AIQ-21-GR shows high levels of reliability and validity. The results confirmed high scores of internal consistency (Cronbach’s α = 0.91) and indicated good known—groups validity (Mann–Whitney U = 202, p < 001). Content validity achieved high scores with an overall median score of 4 [Q25 = 4, Q75 = 5]. The psychometric properties of the AIQ-21-GR support the reliability and validity of the tool for investigating the impact of aphasia on the quality of life of Greek-speaking PWA. The AIQ-21-GR can be used for setting functional goals in collaboration with PWA and as a patient reported outcome measure for functional communication training.
Keywords: AIQ-21-GR; Aphasia assessment; People with aphasia (PWA); Tool validation; Stroke